Spatial change in German online food retailing: Examples from brick-and-mortar, pure-play and combined e-commerce - Dederichs, Sebastian; Dannenberg, Peter (Raumforschung und Raumordnung | Spatial Research and Planning, 2021)
Even before the current covid-19-pandemic, online grocery retailing in Germany is achieving a high level of momentum, giving rise to new and increasingly hybrid forms of operation and distribution models in the retail sector. These new operational forms of complementary, pure and combined e-commerce are accompanied by spatial changes of the individual value-added steps, e.g. in the areas of logistics, store structure and transfer of goods, which have hardly been investigated so far. Using three selected cases studies (Picnic, Wochenmarkt24 and Rewe) newer types of spatial logistics and distribution structures were identified and different location factors of these were listed. Thus, the paper illustrates that, in addition to the typical factors of location selection for distribution warehouses (proximity to customers, employees and suppliers) in food retailing, other aspects, such as a shortening of the last mile, a minimum or maximum density of households in the surrounding area or the proximity to an (agricultural) producer structure, can also be of importance for the new forms of operation.